COPD, exacerbation and self-management: a literature review. (2nd February 2022) - Boyer, Paula
Abstract : The incidence of COPD is rising in the UK. Paula Boyer looks at the evidence for the self-management of COPD and how this can help manage exacerbations Chronic obstructive pulmonary disease (COPD) is being increasingly diagnosed in the UK, and is expected to continue to rise due to an ageing population with multiple co-morbidities and exposure to risk factors, such as cigarette smoke, noxious gases and air pollutants. The prevalence of this disease is high in areas of socioeconomic deprivation and among highly industrial areas. The use of self-management plans in COPD is recommended by the National Institute for Health and Care Excellence (NICE), to enable patients with this disease to be competent and confident in taking part in managing their own health condition and recognising signs and symptoms of an exacerbation. The aim of this article is to discuss self-management of COPD and the clinical guidance surrounding exacerbation of disease.